Leverage dynamics and the burden of debt - Mikael Juselius; Mathias Drehmann (Bank of Finland, 2016)
In addition to leverage, the debt service burden of households and firms is an important link between financial and real developments at the aggregate level. Using US data from 1985 to 2013, we find that the debt service burden has sizeable negative effects on expenditure. Its interplay with leverage also explains several data puzzles, such as the lack of above-trend output growth during credit booms and the depth and length of ensuing recessions, without appealing to large shocks or non-linearities. Using data up to 2005, our model predicts paths for credit and expenditure that closely match actual developments before and during the Great Recession.
URN:NBN:fi:bof-201604051073
Keywords: E20; E32; E44; G01; 330